PENGARUH SUBSTITUSI TEPUNG UBI JALAR ORANGE TERHADAP (Ipomoea batatas) KUALITAS PUTU AYU - YENI, WIWIK INDRA; Syarif, Wirnelis; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
This research aimed to analiyze the different effect of orange sweet potato flour which composition are 0%; 15%; 25%; 35% to the quality of shape, colour, flavor, texture and taste of putu ayu. The kind of the reseach was experimental using complete random design with one factor which the amount of orange sweet potato flour 0%; 15%; 25%; and 35% with 3 times experimental repeatedly, done in the Tata Boga DepatementÂ Home Economic Faculty of Engineering Padang State University Workshop in the month of October 2013. The hypothesis showed that there was an effect to the substution of orange sweet potato flour which 0%; 15%; 25%; and 35% to the putu ayu quality. The test levels substitution orange sweet potato flour shows the best quality in terms of shape located at 0% (X0) without the addition of orange sweet potato flour with exact form category, in term of colour located at 35% (XÂ3) with beige brown category, in term of flavour located at 35% (X3) with essence orange sweet potato flour category, in term ofÂ texture it is located at 0% (X0) with soft category, interm of the taste orange sweet potato flour located at 35% (X3) with a dominan orange sweet potato flour taste category, in term of sweetness taste is located at 35% (X3) with a sweet taste category. The best quality located at (X3) which the orange sweet potato flour is 35%. Keyword: orange sweet potato flour, putu ayu quality